School Counselors’ Social Support and Career Adaptability: The Mediating Role of Career Decision-Making Self-Efficacy and Gender among High School Students - Dwi Jayanti Ariani; Binti Isrofin (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
Career adaptability is a key psychosocial resource for students navigating educational and occupational transitions. This study examined the relationship between school counselors’ social support and career adaptability, and the mediating role of career decision-making self-efficacy (CDMSE), with gender as a moderator. A quantitative correlational design involved 330 Grade XII students from public senior high schools in Semarang, Indonesia. Data were collected using validated Likert-type scales measuring school counselors’ social support, CDMSE, and career adaptability. Analysis used PROCESS Macro Model 5 with bootstrapping. Result showed that school counselors’ social support significantly predicted both CDMSE and career adaptability. CDMSE was positively associated with career adaptability and significantly mediated the relationship between social support and career adaptability. However, gender did not moderate the direct effect of social support on career adaptability. These findings highlight the importance of strengthening students’ confidence in career decision-making through sustained counselor support to promote long-term career adaptability.